2D Ruddlesden–Popper Perovskite Single Crystal Field‐Effect Transistors. (24th September 2020) - Liu, Fengjing; Wang, Liang; Wang, Jiawei; Wang, Feng; Chen, Yiyi; Zhang, Shuai; Sun, Huijuan; Liu, Jia; Wang, Gongtang; Hu, Yuanyuan; Jiang, Chao
Abstract: 2D Ruddlesden–Popper perovskites (2D PVKs) have attracted huge interest because of their excellent optoelectronic properties, yet the understanding of their electrical properties is inadequate due to the difficulties in obtaining 2D PVK field‐effect transistors (FETs) with decent performance. Herein, the fabrication and characterization of 2D PVK ((BA)2 (MA) n −1 Pb n I3 n +1 ) single crystal FETs are reported, which exhibit reliable field effect electrical characteristics at low temperatures. Kelvin probe force microscopy (KPFM) results reveal that both ion migration and contact resistance seriously degrade device performance. While ion migration can be suppressed at low temperatures, contact resistance seems to fundamentally determine device performance. On one hand, Schottky contacts are observed to form at the metal/2D PVK interface because of Fermi level pinning, resulting in significant charge injection resistance, although this can be remarkably improved by replacing Au electrodes with Ca. On the other hand, the out‐of‐plane mobility is found to be three orders of magnitude lower than the in‐plane mobility in 2D PVKs, causing large interlayer transport resistance. Thus, a low work‐function metal and a thin crystal are important for achieving high device performance. This work provides important experimental insights into fabrication and electrical properties of 2D PVK FETs. Abstract : 2D PVK ((C4 H9 NH3 )2 (CH3 NH3 ) n −1 Pb n I3 n +1 ) single crystal field‐effect transistors show obvious n‐type transistor behavior and high on‐off ratio at low temperatures. Metal/semiconductor contacts and interlayer transport are found to be two important factors seriously limiting the device performance besides ion migration. A low work function metal like Ca and a thin 2D PVK crystal are preferred for achieving high‐performance transistor devices.